EARNING PER SHARE DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING TAHUN 2018-2021 - Dwitama, Andika; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Food and beverage companies are companies that can advance the economy in Indonesia. When viewed from its role, food and beverage companies are the basic needs of society. The large population makes the level of public consumption of food and beverage companies continue to increase. The purpose of this study was to test and analyze the Earning Per Share and Debt to Equity Ratio on stock returns in food and beverage companies listed on the IDX through dividend policy. Data analysis and data testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test obtained from the Smart PLS 3.0 application show that Earning Per Share has a negative but insignificant effect on dividend policy. Debt to Equity Ratio has a significant positive effect on dividend policy. Earning Per Share and Debt to Equity Ratio have a negative but insignificant effect on stock returns. Dividend policy has a negative but insignificant effect on stock returns. The results of the indirect effect hypothesis test show that Earning Per Share has a positive but insignificant effect on stock returns through Dividend policy, Debt to Equity Ratio has a negative but insignificant effect on stock returns through dividend policy, but has a significant effect on stock returns through dividend policy.